Cellular immune response in chickens infected with avian infectious bronchitis virus (IBV). (April 2017) - Zhang, Tong; Li, Deyin; Jia, Zhihua; Chang, Jianyu; Hou, Xiaolin
To understand the mechanistic basis of innate immunity against the infectious bronchitis virus (IBV), the gene transcription profile of pattern recognition receptors (PRRs) in SPF chicken tissues infected with an IBV-M41 strain was examined. IBV infection induced mRNA transcription of TLRs, RLRs, and NODs. TLR7, MyD88, TRAF6, MDA5, LGP2, and NLRC5 were stimulated, as well as mRNA activation of the downstream genes of NF-κB and IRF3. And mRNA for the pro-inflammatory cytokines of interferon-α (IFN)-α, IFN-β, tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) showed over-expression. The IBV load in tissues gradually reduced. These results suggested that the three kinds of PRRs signaling pathways and innate immune cytokine were induced after IBV infection.